David Derksen - Derksen, David (Base Diseño e Innovación, 2015)
Nature and, particularly, the principles and processes within it, are the source of inspiration for David Derksen. The result is a strong emphasis on materials, in how they behave and how they can be built. According to Derksen, producing objects is like playing with the forces of nature. In his work, he attempts to express the beauty of materials and the processes by which these are produced.